Persecution and repression of religious scholars by the Soviet authoritie in Uzbekistan - Arslonbekov Nursultan (Genius Journals, 2022)
The article describes the tragic fate of religious scholars who were persecuted and oppressed by the penal authorities of the Soviet government in the 1920s and 1930s.
Keywords: Soviet government; penitentiaries; religion; cleric